Comparative Study on The Shaping Ability of Three Reciprocating Nickel-Titanium Single File Systems in Curved Root Canals - Sanguanwongthong, Phanthanan; Taweewattanapaisan, Peeraporn; Sakdee, Jaruma; Piyachon, Chinalai (Khon Kaen University Dental Journal, 2020)
The purpose of this study was to compare the shaping ability of Reciproc® blue, WaveOne® Gold and EdgeOne Fire™ Reciprocating nickel-titanium single file systems in curved root canals. A total of 45 root canals in extracted human teeth with angles of curvatures ranging from 20-40 degrees and radii ranging between 5-9 mm were divided into 3 groups (n = 15). The degree of canal transportation distances were evaluated using micro-computed tomography (Micro-CT). The percent change of degree of canal curvature after root canal preparation was also evaluated using digital radiography. The overall preparation times were recorded. The degree of canal transportation distances and percent change of degree of canal curvature after canal preparation were analyzed statistically using the Kruskal–Wallis test. The preparation times were analyzed using One-Way ANOVA with a 95% confidence level. The results showed no statistically significant differences in the degree of canal transportation distances and preparation times between 3 groups. The EdgeOne Fire™ system recorded a more statistically significant percent change of canal curvature than the WaveOne® Gold system. The mean preparation time was 72.1-74.4 seconds per canal. In conclusion, the 3 groups of Reciprocating nickel-titanium single file systems showed favorable results in terms of the shaping ability of curved root canals. All groups produced only minor changes in canal curvature, while the EdgeOne Fire™ system showed more of a decrease in the angle of canal curvature than the WaveOne® Gold system.